Detection of Influenza A viruses at migratory bird stopover sites in Michigan, USA. Issue 1 (1st January 2018) - Lickfett, Todd M.; Clark, Erica; Gehring, Thomas M.; Alm, Elizabeth W.
ABSTRACT: Introduction: Influenza A viruses have the potential to cause devastating illness in humans and domestic poultry. Wild birds are the natural reservoirs of Influenza A viruses and migratory birds are implicated in their global dissemination. High concentrations of this virus are excreted in the faeces of infected birds and faecal contamination of shared aquatic habitats can lead to indirect transmission among birds via the faecal-oral route. The role of migratory birds in the spread of avian influenza has led to large-scale surveillance efforts of circulating avian influenza viruses through direct sampling of live and dead wild birds. Environmental monitoring of bird habitats using molecular detection methods may provide additional information on the persistence of influenza virus at migratory stopover sites distributed across large spatial scales. Materials and methods: In the current study, faecal and water samples were collected at migratory stopover sites and evaluated for Influenza A by real-time quantitative reverse transcriptase PCR. Results and Discussion: This study found that Influenza A was detected at 53% of the evaluated stopover sites, and 7% and 4.8% of the faecal and water samples, respectively, tested positive for Influenza A virus. Conclusion: Environmental monitoring detected Influenza A at stopover sites used by migratory birds.